Optimalisasi Pemanfaatan Transportasi Udara Bandara Aek Godang dan Bandara Jenderal Besar AH Nasution untuk di Sumatera Utara - Akbar, Bill; N, Zulkifli (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to evaluate the utilisation and development potential of Aek Godang Airport in North Padang Lawas Regency and JB AH Nasution Airport in Mandailing Natal Regency in supporting regional air transport in North Sumatra. The method used is SWOT analysis with AHP weighting to determine development priorities. The results showed that JB AH Nasution Airport has greater external opportunities with an EFAS score of 3.94, while Aek Godang Airport excels in internal strengths with an IFAS score of 4.03. This research focuses more on the supply side, highlighting the infrastructure readiness of both airports. JB AH Nasution Airport is recommended to be developed as a primary airport with a focus on long-haul and international routes, while Aek Godang Airport is geared as a secondary airport for regional routes and cargo logistics. Synergy between the two airports is essential to create an efficient air transport system and support sustainable regional economic growth.